'In numbers we trust': Statistical data as governing technologies in the era of student achievement and school accountability. Issue 9 (8th August 2022) - Kim, Jonghun
Abstract: This study examines the Programme for International Student Assessment (PISA), one of the most influential tools of global education reform discourses in the 21st century. The study focuses on the governing role of statistical data in the discourse constructed by the international comparative assessment, referring to the global educational governance of the OECD. Disturbingly, the systematic collection and distribution of data does not merely quantify student achievement. Rather, students and participating countries are also qualified and classified. Here, OECD's PISA statistics act as a governing technology enabling the comparisons; through PISA's statistics, the OECD has largely fostered the test-driven education reform trends worldwide. In this study, statistical data are examined as political instruments visualizing intangible concepts, constructing definitions of good practice and improvement, and fabricating the individuals whose knowledge and skills are normalized. In conclusion, it is necessary to rethink the new sociopolitical instrument – PISA's statistics – not as a master rationale to reform the educational system of each country, but as a mere reference point based on the system's distinctiveness.